WHEN HAIR TALKS: HOW HAIRSTYLES INFLUENCE THE PERSONALITY OF THE MAIN CHARACTER IN THE K-DRAMA ADAPTATION OF THE WEBTOON PERFECT MARRIAGE REVENGE - Yusuf, Julia Absara; Saputri, Hanna Dorina Riska; Dewi, Sellyana Tungga (UIN Raden Mas Said Surakarta, 2024)
Hair plays a crucial role in a woman's identity, serving both aesthetic and expressive purposes, and often reflecting personality traits (Cunningham et al., 1997). This study explores the changes of stereotypes associated with hair types and colors in the Korean drama adaptation entitled Perfect Marriage Revenge from a Webtoon series. Using Hutcheon's (2013) adaptation theory and Cunningham et al.'s (1997) insights on hair and personality, The research examines how haircolors in the drama adaptation differs from the original Webtoon series and how it affects the character’ss personality. Cunningham et al. (1997) suggested that hair colors influences characteristics: blonde hair is seen as feminine, attractive, and emotional, while brunette hair is linked to intelligence and structure. This qualitative study analyzes visual and textual data from both the Webtoon and K-Drama, employing a comparative method to identify differences in hairstyles and character portrayals. Findings reveal that Han Yi Joo's character undergoes a transformation influenced by changes in hair color in both the original and adapted works. The changes also happen in the personality of the same character, which means that the adaptation version takes in to account both hair color and its stereotype.